Analisis Peta Aglomerasi Industri Kecil Menengah di Kecamatan Mojoagung Kabupaten Jombang - Faiz Naufal Al Hanani; Lucky Rachmawati (Jurnal Ekonomika : INDEPENDEN, 2022)
Economic development is one of the important indicators in regional development. The large number of Small and Medium Industries (IKM) spread across Indonesia has great potential to support domestic economic development and improve people's welfare. This study aims to determine the agglomeration mapping of Small and Medium Industries (IKM), as well as to study further related factors that cause the agglomeration of Small and Medium Industries (IKM) in Mojoagung District, Jombang Regency. The type of research used is descriptive qualitative research. The results of this study indicate that the agglomeration of Small and Medium Industries (IKM) in Mojoagung District, Jombang Regency tends to agglomerate in Dukuhmojo Village, Karangwinongan Village, Mojotrisno Village, and Mancilan Village, as well as the factors that cause the agglomeration of Small and Medium Industries (IKM), namely the factor of Raw Materials, Manpower, Marketing. and Accessibility.